The Relation of Corporate Governance to Audit Quality: Case Study on Non Financial Companies - Al MhdiAbulgasim Abusbaiha (Conference In Business, Accounting, And Management (CBAM), 2015)
This study is aimed to know the factors that affect the quality of audits on non financial companies in Indonesia. This study uses the financial statement of non financial companies listed in Indonesia Stock Exchange (IDX) for period of 2013-2014. Data collection method used in  this   research  is   purposive  sampling   with   31   non   financial companies as the sample. The hypotheses were tested using logistic regression analysis. The results show that the variables that have a significant effect on audit quality is a measure of independent board. While other variables examined in this study such as Institutional Ownership is  not proven to affect on audit quality.Keywords: Managerial Ownership, size independent board, audit committee size and audit quality